2022
DOI: 10.3390/plants11101309
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Complexity of Type-IV Trichome Development Reveals the Steps towards an Insect-Resistant Tomato

Abstract: The leaves of the wild tomato Solanum galapagense harbor type-IV glandular trichomes (GT) that produce high levels of acylsugars (AS), conferring insect resistance. Conversely, domesticated tomatoes (S. lycopersicum) lack type-IV trichomes on the leaves of mature plants, preventing high AS production, thus rendering the plants more vulnerable to insect predation. We hypothesized that cultivated tomatoes engineered to harbor type-IV trichomes on the leaves of adult plants could be insect-resistant. We introgres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…Although some individual loci were sufficient for the appearance of type-IV trichomes, the simultaneous presence of the five loci appears to be necessary to increase type-IV trichome density. However, MT- Get plants did not exhibit the same level of resistance to whiteflies as observed in S. galapagense (Firdaus et al, 2013; Firdaus et al, 2012; Vosman et al, 2019; Vendemiatti et al, 2022). Since both the density of type-IV trichomes as well as the levels of AS in MT- Get were inferior to those observed in S. galapagense , it was concluded that there are additional genetic factors linked to insect resistance in S. galapagense , which is likely to be a complex, polygenic trait.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Although some individual loci were sufficient for the appearance of type-IV trichomes, the simultaneous presence of the five loci appears to be necessary to increase type-IV trichome density. However, MT- Get plants did not exhibit the same level of resistance to whiteflies as observed in S. galapagense (Firdaus et al, 2013; Firdaus et al, 2012; Vosman et al, 2019; Vendemiatti et al, 2022). Since both the density of type-IV trichomes as well as the levels of AS in MT- Get were inferior to those observed in S. galapagense , it was concluded that there are additional genetic factors linked to insect resistance in S. galapagense , which is likely to be a complex, polygenic trait.…”
Section: Introductionmentioning
confidence: 71%
“…The Get02/Wo parental line, MT- Get , exhibits several traits that could affect agronomical performance, such as reduced fruit weight (Vendemiatti et al, 2022). Therefore, we evaluated Get02/Wo performance also because there is a concern that breeding based on high trichome densities and enhanced specialized metabolism may negatively impact yield due to the deviation of energy from primary metabolism that contributes to fruit size and, partially, to taste (Tieman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations